Intracranial Cisternal Lipoma Associated with Cerebellar Cortical Dysplasia Diagnosed Using Dixon Technique: A Case Report and a Review of Literature - Hwang, Minhee; Park, Hyun; Baek, Hye J.; Ryu, Kyeong Hwa; Cho, Eun; Yoon, Seokho (Current Medical Imaging, 2022)
Background: Intracranial lipomas are very rare congenital malformations. Previous studies have shown various brain anomalies related to intracranial lipomas, most of which are agenesis or dysgenesis of the adjacent structures. To the best of our knowledge, cortical dysplasia related to intracranial lipoma has yet to be reported. Case Report: We present a rare case of intracranial lipoma in the quadrigeminal and superior cerebellar cisterns with combined cerebellar cortical dysplasia. A 43-year-old female underwent brain MRI to identify possible cause of headache. We made a confident diagnosis based on MR findings using Dixon technique, which is a fat-water separation method based on chemical shift. We also identified unique combined abnormalities of the right cerebellar hemisphere near the cisternal lipoma that showed an abnormal vertical orientation of the cerebellar folia and disorganized parenchymal Conclusion: This case exhibits the rareness of the intracranial lipoma related cerebellar cortical dysplasia by reviewing relevant literature and also highlights the usefulness of Dixon techniques in daily clinical practice.
Keywords: dixon technique